Acompanhamento do controle de qualidade das argamassas colantes na empresa Brasil química e mineração industrial Ltda. – Mossoró/RN - Monteiro, Tayná Souza (Universidade Federal Rural do Semi-Árido, 2019)
Mortars are building materials that have adhesion and coating properties, these are obtained from the mixture of sand, water, binders and may also have the addition of minerals and contain additives, in order to give them specific properties. According to their purpose, mortars can be adhesive, coating, grouting and finishing. This paper aims to follow the different analyzes that are performed in the control of mortars in the company Brasil Química e Mineracao Industrial Ltda., Located in the municipality of Mossoró / RN. The purpose of the company is the production and sale of mortars, smooth and rustic acrylic texture, PVA run paste, machined concrete, plasticizers, release agents, grouts, additives and waterproofing, all of which are of great importance in civil construction. The company also aims to use waste from various segments in products for construction and for the oil and gas industry. The tests performed for quality control were granulometry, additive testing, open time and tensile strength, where it was found that all the mortars analyzed were in compliance with the required standards.
Monografia
Keywords: Argamassa; Análises; Controle de qualidade; ENGENHARIAS::ENGENHARIA QUIMICA